La guitarra en la música tradicional Suramericana (2024)
This project investigates two distinctive musical genres from South America: San Juanito and Huayno, both representative of the Andean music tradition. The project focuses on composing a San Juanito in its traditional format and adapting a classic Huayno to a solo format using live looping. These genres reflect the cultural identity and diversity of communities in Ecuador, Colombia, Peru, Bolivia, Argentina, and Chile.